Hydro-biogeochemistry transport of black carbon project-data - Cotrufo, Francesca (Colorado State University. Libraries, 2015)
This data package was produced by researchers working on the Hyrdo-Biogeochemistry Transport of Black Carbon Project. This project was supported by National Science Foundation and the Water Institute at Colorado State University. This data package includes a tab-delimited data table and an accompanying tab-delimited file (file name ending in "_var') that denotes header definitions and data types for each column in the data table. Detailed metadata also are contained within an Ecological Metadata Language document (i.e. XML). Black carbon (BC) is a ubiquitous component of the carbon cycle, yet controls on its landscape-level distribution, including the relative importance of mechanisms for transport across the terrestrial aquatic interface, are relatively unknown. In June 2012, the High Park Fire (HPF) burned 353 km2 of land in the Cache la Poudre (CLP) watershed just northwest of Fort Collins, CO. Following independent efforts of our group to quantify the effects of the HPF on biogeochemical pools and landscape geomorphology, we aimed to synthesize our respective datasets with two main objectives: 1. determine and relate BC content in different parts of the watershed including litter, soils, river bank sediments and dissolved and particulate organic materials in river water, 2. develop a conceptual framework for mechanisms that contribute to BC export from the CLP on short and long-term time scales. Using the benzene polycarboxylic acid (BPCA) method as a molecular proxy for BC concentrations, we found that the majority of BC deposited on the landscape by the HPF was located in the litter, coarse plant fraction of river bank sediments, and DOC, suggesting that BC mobilized on the landscape is transported downstream through the river network. We also participated in a comparative study to investigate differences between the BPCA method and stable polycyclic aromatic carbon and benzene polycarboxylic acid method. The results of the comparative analysis are included in this data table and this work was supported by an NSF grant for Catalyzing New International Collaborations.
BCINT_BPCA_SPAC IR_comp_rev151026 - data table
This data package includes a tab-delimited data table and an accompanying tab-delimited file (file name ending in '_var') that denotes header definitions and data types for each column in the data table.
Metadata describing the data will be created in Ecological Metadata Language. A data package, including the data values and a metadata file, will be co-located within a landing page, which will be assigned a persistent identifier from Handle.net and include suggested citation verbiage.
This was a data set produced from scientific studies conducted on the High Park Fire.
Department of Soil & Crop Sciences
Keywords: black carbon; terrestrial aquatic interface; High Park Fire; Cache la Poudre watershed